Structural language in neurodevelopmental disorders: comparison between autism spectrum disorder (ASD) and developmental language disorder (DLD) - Andreou, Georgia; Lymperopoulou, Vasiliki; Aslanoglou, Vasiliki (Frontiers in Education, 2025)
IntroductionThe aim of the present study is to investigate structural language of children with Autism Spectrum Disorder (ASD) and Developmental Language Disorder (DLD) in a Greek-speaking population.MethodsThree groups participated in the study, matched for age and sex: 25 children with ASD aged 6–8 years (mean age 84.19 months; SD = 6.55), 25 children with DLD aged 6–8 years (mean age 84.09 months; SD = 6.72), and 25 typically developing children, who served as controls (mean age 84.09 months; SD = 6.72). Structural language was examined in all three groups by using standardized tests assessing their skills in phonological awareness, morphosyntax and vocabulary. Phonological skills were evaluated using subscales from the Test for the Detection and Investigation of Reading Difficulties, while scales from the Diagnostic Test of Linguistic Intelligence for school-age children were used for the assessment of morphosyntax. Finally, the lexical scale from WISC-V was used to assess expressive vocabulary.ResultsThe findings of the study showed that both children with ASD and children with DLD performed worse on tests examining structural language than their typically developing peers. More specifically, statistically significant differences were observed across all measurements (p < 0.001). However, the comparison between the two clinical groups revealed that the performance of children with DLD was worse than that of children with ASD on all tests examining structural language. More specifically, the difference between the two groups in terms of phonology and morphosyntax was p < 0.001, while the difference in terms of expressive vocabulary was p = 0.03.DiscussionThe findings shed light on important aspects of structural language in both ASD and DLD by providing insights into the common and differential language challenges faced by individuals with these neurodevelopmental disorders. This analysis enhances the understanding of language development in the Greek-speaking population and offers a cross-disorder approach. These findings may contribute to the development of targeted educational strategies to support children with ASD and DLD.